Retroplacental hematoma: epidemiological profile and associated risk factors among Malagasy women at the Soavinandriana Hospital Center (CENHOSOA) - Ranjandriarison, Dorland T.; Rakotondraibe, Aurelien M.; Rakotovao, Henintsaina A.; Raelison, Jasper G.; Rabarikoto, Hary F.; Randriamahavonjy, Romuald (International Journal of Research in Medical Sciences, 2025)
Background: Retroplacental hematoma (RPH) is a severe obstetric emergency that increases maternal and fetal morbidity and mortality. Data on RPH remain scarce in Madagascar. This study aimed to determine its prevalence and identify associated risk factors. Methods: A descriptive and analytical case–control study was conducted in the Department of Obstetrics and Gynecology, Soavinandriana Hospital Center (CENHOSOA), Antananarivo, from January 2020 to December 2024. Sixty RPH cases and 120 controls (2:1 ratio) were analyzed. Data were retrospectively collected from medical records and analyzed using Epi Info 7.2. Associations were assessed using odds ratios (OR) with 95% confidence intervals (CI). Results: Among 5,921 deliveries, 60 cases of RPH were identified (prevalence 1.01%). The mean age was 28.7 years (17-40). Farming was significantly associated with RPH (p=0.001; OR=5.75; 95% CI: 1.92-17.21). Lack of antenatal care (p=0.001; OR=6.51; 95% CI: 1.97-21.44), hypertension/preeclampsia (p=0.000; OR=5.68; 95% CI: 2.8-11.5), and abdominal massage during pregnancy (p=0.000; OR=13.57; 95% CI: 5.15-35.73) were major risk factors. Preterm delivery (<37 weeks) was significantly related to RPH (p=0.000; OR=7.97; 95% CI: 3.91-16.25). Cesarean section was required in 83.3% of cases (p=0.000; OR=23.57; 95% CI: 10.31-53.85). Conclusions: RPH prevalence in this study was higher than reported in other regions. The main risk factors were abdominal massage, hypertensive disorders, absence of antenatal care, and low socioeconomic status. Strengthening antenatal follow-up and discouraging harmful traditional practices may reduce RPH-related complications.